Harmonizing Khilafiyah of Tarāwīh Prayer from the Perspective of the Kitab Kasyfu at-Tabārih fī Bayāni Ṣalāt at-Tarāwīh by KH. Abul Faḍol as-Senūri at-Tūbāni - Nafi, Moh. Iqbal (Lembaga Pengembangan Pesantren dan Diniyah Provinsi Jawa Timur, 2024)
The practice of tarawih prayer is inseparable from the influence of local communities' history, culture, and traditions, which creates variations in practice in different regions. There are differences of opinion regarding the number of rak'ahs and the procedure for performing tarawih prayers, especially in Indonesia, where some follow 8 rak'ahs. In comparison, others follow 20 rak'ahs, each with a different basis. This article aims to provide an in-depth understanding of these differences and examines the kitab Kasyfu at-Tabārih fī Bayāni Ṣalat at-Tarāwīh by KH. Abul Faḍol bin Abdus Syakur as-Senūri at-Tūbāni, which thoroughly explores the tarawih prayer. This literature research was conducted using an analytical descriptive approach, examining related texts and documents. The study's findings indicate that the differences in the number of rak'ahs and procedures of the tarawih prayer result from different interpretations of the Prophetic traditions and the practices of the Companions. This research is expected to enrich Islamic insights and reduce the potential for intergroup conflict within Muslims regarding the implementation of tarawih prayers.